Pengaruh Pengaruh Kegiatan Ekstrakurikuler Rohis (Rohani Islam) terhadap Tingkah Laku Siswa di SMPN 1 Kota Bogor - Novi Novi Novi; Fahmi Irfani; Suyud Arif (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2024)
The purpose of this research namely: (1) to determine the extracurricular activities of rohis at SMPN 1 Bogor City, (2) to determine the behavior of students at SMPN 1 Bogor City, (3) to find out whether there is a significant influence between extracurricular activities of rohis on the behavior of students at SMPN 1 Bogor City. The data collection technique used is a questionnaire by distributing data to students who take part in extracurricular activities at SMPN 1 Bogor City, for the method used, namely surveys. The results of this study show that: (1) rohis extracurricular activities are included in the category of quite high, (2) student behavior is included in the fairly high category, (3) there is a positive and significant influence between extracurricular activities on student behavior at SMPN 1 Bogor City with a significance value of 0.000 < 0.05 then indicated by (R) which is 0.559 which is in the medium or sufficient category, because it is located between 0.40-0.60. The percentage of influence of the independent variable on the dependent variable called the coefficient of determination (R2) is 0.313 or 31.3%. Keywords: Activities, Spirit, Behavior.